A Novel DPYD Variant Associated With Severe Toxicity of Fluoropyrimidines: Role of Pre-emptive DPYD Genotype Screening - Tong, Chi C.; Lam, Ching W.; Lam, Ka O.; Lee, Victor H. F.; Luk, Mai-Yee (Frontiers in Oncology, 2018)
Background: The fluoropyrimidine anticancer drug, especially 5- fluorouracil (5-FU) and its prodrug capecitabine are still being the backbone of chemotherapeutic regimens for colorectal cancer. Dihydropyrimidine dehydrogenase (DPD) is the key enzyme for the catabolism of 5-FU. Over the past 30 years, there are substantial clinical evidences showing that DPD deficiency is strongly associated with severe and fatal fluoropyrimidine-induced toxicity. Patients and methods: A 49 year old lady with resected stage III carcinoma of sigmoid colon was scheduled to have a course of 5-FU based adjuvant chemotherapy. She developed unexpected acute severe (grade 4) toxicity after the first cycle of chemotherapy. Genomic DNA was isolated from three ml peripheral blood cells for full sequencing of DPYD (the gene encoding DPD). Results: Exome sequencing confirmed that she is heterozygous for NM_000110.3:C.321+2T>C of the DPYD gene. To the best of our knowledge, this variant is a novel pathogenic splicing variant of the DPYD gene resulting in a non-functional allele. As she has a heterozygous genotype and considered having decreased DPD activity, we followed the international recommendation and restart chemotherapy with at least 50% reduction for 5-FU dose. We then titrate the 5-FU dose and the patient tolerated the subsequent cycles of chemotherapy and completed the whole course of adjuvant chemotherapy. Conclusions: With pre-emptive test on DPD deficiency prior to the administration of the fluoropyrimidine drugs, the aforementioned patient’s life threatening event could be avoided. This clinical utility has been confirmed by two recent large-scale studies and called for a drug label update.